Are body posture and self-reported musculoskeletal symptoms different between employees in the healthcare and administrative sectors? - Silva, Bruno; Maduro, Paula; Silva, Tarcísio; Trombini-Souza, Francis (Work, 2019)
BACKGROUND: Several professionals in hospitals can be affected by work-related musculoskeletal disorders (WMSDs). OBJECTIVE: To evaluate and compare the body posture and self-reported musculoskeletal symptoms of employees in the healthcare and administrative section of a university hospital. METHODS: Body posture and self-reported musculoskeletal symptoms of 106 employees were quantitatively evaluated. The sample was divided into two groups: health care group (HCG) composed of 57 professionals (88% were females) with an average age of 34±7 years, mass of 66.52±14.78 kg, height of 1.62±0.07 m, and body mass index (BMI) of 25.37±4.50 kg/m2; and the administrative section group (ADMG) composed of 49 professionals (57% were females) with an average age of 30±7 years, mass of 74.90±14.12 kg, height of 1.68±0.09 m, and BMI of 26.76±4.40 kg/m2. RESULTS: The only significant difference between groups for the body posture was the greater right Q-angle in the CG (p = 0.039). Self-reported musculoskeletal symptoms in the seven days prior to assessment were not associated with work section. CONCLUSION: The work section within the university hospital did not influence body posture or self-reporting of musculoskeletal symptoms among the healthcare and administrative staff.